Summary of reports on unratified conventions and on recommendations. (Article 19 of the Constitution). Discrimination in respect of employment and occupation. International Labour Conference. Forty-seventh session, Geneva, 1963. Report III (part II) (International Labour Office, 1963)
Information and reports on the application of conventions and recommendations.